PENGARUH MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. BANK DANAMON UNIT SIMPAN PINJAM BATURAJA - DYAH AYU PUTRIANI; RENDY WAHYU OGANTA (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
This study discusses the influence of motivation and compensation on the performance of employees at PT. Bank Danamon Unit Simpan Pinjam Baturaja. The analysis used is multiple linear regression analysis, t test, F test, and coefficient of determination. The results of the analysis indicate that motivation and compensation on the performance of employees at PT. Bank Danamon Unit Simpan Pinjam Baturaja affect either partially or simultaneously. Results of the analysis of determination (R2) shows that the coefficient of determination (R) motivation (X1) and compensation (X2) amounted to 60.9% influence on employee performance (Y) while the remaining 39.1% influenced or varied by other variables , Researchers suggest the company in order to remain consistent with the targets to be achieved by employees and implement motivation of employees and improve compensation through the provision of appropriate and fair bonuses so that employees are willing to improve its performance.